Perlindungan ABK Indonesia Yang Bekerja Di Kapal Asing Berdasarkan Unclos 1982 - Wahyuni Boeng; Arman Anwar; Richard Marsilio Waas (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: This study discusses the legal review of the protection of Indonesian crew members working on foreign ships based on UNCLOS 1982 related to cases of environmental pollution carried out by South Korean ships in the Strait of Hormus, Persian Gulf, Iran involving 2 (two) Indonesian crew members in hold by Iran.Purposes of the Research: Analyze the detention of crew members in accordance with international law and analyze the responsibility of the Indonesian government in the process of releasing and repatriating Indonesian crew members detained by the Iran government.Methods of the Research: This research uses the juridical normative method by using a statutory approach, a conceptual approach, and a case approach.Results of the Research: The results showed that the detention by the Iranian government of the ship and crew of Hankook Chemi, South Korea was in accordance with international law based on the provisions of Article 73 of UNCLOS 1982, namely that the coastal State has the authority to enforce the legislation of the coastal State. However, the Indonesian government also has the right to provide legal protection to Indonesian crew members. The forms of protection of the Government of Indonesia consist of 3, namely: technical protection, juridical protection, and political protection, based on the Law of the Republic of Indonesia Number 39 of 2004 concerning the placement and protection of Indonesian workers abroad.